Paying attention to the semantic nuances of the text - قادر, کاروان عومەر; نبی, ڕێبوار احمد (Sulaimani Journal for Humanities, 2020)
This dissertation under the title “prototype perspective in cognitive semantics” is an empirical analytical investigation addressing the realization of prototypes as typical examples of categories and concepts within cognitive semantics in language in general and Kurdish language. this research includes three major chapters, concludes that; categories through some cultural and dynamic processes turn to prototypes within the boundaries of a speech community. This illustrates the nature and way the mental/cognitive abilities work with regard to classifying the types and categories which also seem applicable to the teaching programs.